Antibiogram and MDR Pattern of the Bacterial Isolates from German Cockroaches (Blattella germanica L.) at RMCH, Rajshahi, Bangladesh - Akter, M. S.; Islam, M. S.; Mohanta, M. K.; Parvin, S. (Journal of Scientific Research, 2023)
German cockroaches, Blattella germanica L. are the most dangerous pests in hospital environments which cause diseases like food poisoning, dysentery, and diarrhea. Antibiogram and multidrug resistance (MDR) patterns of the bacterial isolates from the cockroaches inhabiting three Wards of Rajshahi Medical College Hospital, Rajshahi, Bangladesh, were determined. A total of 52 bacterial isolates, 26 from the cuticle and 26 from the gut, comprising 20 (38.5 %) from the Neuromedicine ward, 18 (34.6 %) from the Orthopaedic ward, and 14 (26.9 %) from the Surgery ward, were used for biochemical assays and diagnostic characteristics, where seven Gram-negative rod species were identified. E. coli (n=8 or 40 %), Klebsiella spp. (n=5 or 28 %) and Klebsiella spp. (5 or 35 %) constituted the most dominant bacteria from the three wards respectively. Antibiogram of the bacterial isolates against 18 commonly used antibiotics revealed that Serratia, Klebsiella, Escherichia, and Pseudomonas were resistant to Ceftazidime, whereas Salmonella, Enterobacter, and Proteus were sensitive to the drug. Results of the present study suggest that the German cockroaches might serve as reservoirs for pathogenic and MDR bacteria, which in turn could be responsible for the spread of common food-borne diseases in hospital patients, their attendants, and health professionals.